Renal tubular epithelial cell related partial epithelial-mesenchymal transition in AAⅠ induced renal fibrosis via Wnt7b/β-catenin signaling - Wang, Yi-Fan; Zheng, Dan; Zhang, Ying; Li, Xiao-Fen; Xia, Ming; Tang, Hai-Ming; Huang, Chun-Hua; Li, Mao-Juan; Lou, Di-Dong (Frontiers in Pharmacology, 2025)
IntroductionThis study investigates the pathological progressions in kidneys affected by aristolochic acid nephropathy (AAN) and explores the molecular mechanisms underlying the fibrotic process, specifically focusing on the Wnt7b/β-catenin signaling pathway.MethodsBoth mice and human kidney-2 (HK-2) cells were treated with aristolochic acid I (AAI). In mice, we monitored blood urea nitrogen (BUN), serum creatinine (Scr), kidney injury molecule-1 (KIM-1), pathological modifications of renal tubular epithelial cells (RTECs), and fibrosis degrees during acute/chronic disease phases. Wnt7b/β-catenin expression was evaluated through transcriptome analysis and laboratory assays (immunohistochemistry, Western blotting, immunoelectron microscopy) in acute AAN and cultured cells. Concurrent assays measured representative proteins: Aquaporin 1 (AQP1), Topoisomerase IIα (TOP2A), Vascular Cell Adhesion Molecule-1 (VCAM-1), and α-smooth muscle actin (α-SMA) in chronic AAN RTECs.ResultsAAI increased Scr, BUN, and KIM-1 levels by causing RTEC necrotic shedding in acute stages and promoted renal interstitial fibrosis chronically. Elevated Wnt7b pathway proteins enhanced damaged RTEC regeneration, with regenerated cells expressing mesenchymal proteins VCAM-1 and α-SMA.DiscussionThe Wnt7b/β-catenin signaling pathway connects acute tubule damage to fibrosis, explaining AAN’s pathological continuum. These findings clarify how acute injury progresses to chronic fibrosis in AAN.